Psychometric Validation of a STEAM-Based Knowledge Instrument for Measuring Energy Conversion Concepts in Fifth-Grade Students - Ikhsanudin Ikhsanudin; Ricky Cahyasari Putra; Ade Dwi Putra Janata; Rusdi Febriyanto; Ananda Yhuto Wibisono Putra; R. Ahmad Zaky El Islami; Victor M. Alasa; Jun S. Camara; William J. Triplett (International Journal of STEM Education for Sustainability, 2026)
This study aimed to develop and validate the quality of a multiple-choice instrument for measuring fifth-grade elementary students' understanding of kinetic-to-electrical energy conversion concepts within a STEAM (Science, Technology, Engineering, Arts, and Mathematics) framework. The research employed a Design and Development Research (DDR) approach with systematic instrument development procedures comprising: literature review and blueprint development, item construction, expert validation, field testing with 28 fifth-grade students, and comprehensive psychometric analysis. The instrument consists of 20 multiple-choice items covering three knowledge dimensions: conceptual (5 items), procedural (10 items), and applicative (5 items). Content validity was established through expert review by three science education specialists, yielding a Content Validity Index (CVI) of 0.87. Item analysis revealed difficulty indices ranging from 0.35 to 0.85 (predominantly moderate difficulty) and discrimination indices ranging from 0.30 to 0.75 (good to excellent discrimination). Reliability analysis using Cronbach's alpha produced a coefficient of 0.82, indicating high internal consistency suitable for elementary school assessment contexts. The instrument demonstrates satisfactory psychometric properties aligned with standards for elementary science assessment and effectively integrates STEAM pedagogical approaches.